When the CRC and TCP checksum disagree. - Stone, Jonathan
Traces of Internet packets from the past two years show that between 1 packet in 1,100 and 1 packet in 32,000 fails the TCP checksum, even on links where link-level CRCs should catch all but 1 in 4 billion errors. For certain situations, the rate of checksum failures can be even higher: in one hour-long test we observed a checksum failure of 1 packet in 400. We investigate why so many errors are observed, when link-level CRCs should catch nearly all of them.We have collected nearly 500,000 packets which failed the TCP or UDP or IP checksum. This dataset shows the Internet has a wide variety of error sources which can not be detected by link-level checks. We describe analysis tools that have identified nearly 100 different error patterns. Categorizing packet errors, we can infer likely causes which explain roughly half the observed errors. The causes span the entire spectrum of a network stack, from memory errors to bugs in TCP.After an analysis we conclude that the checksum will fail to detect errors for roughly 1 in 16 million to 10 billion packets. From our analysis of the cause of errors, we propose simple changes to several protocols which will decrease the rate of undetected error. Even so, the highly non-random distribution of errors strongly suggests some applications should employ application-level checksums or equivalents.
Keywords: Computer systems organization; Computer communication networks; Network protocols; TCP IP; Network architecture and design; Packet switching networks; Local and wide area networks; Internet (e.g., TCP/IP).; Design; Measurement; Performance; Reliability; Standardization; Theory